My family and friends are worth their weight in gold: consumer financial decision-making in the context of Brazil - Cordeiro, Rafaela Almeida (2018)
Consumer financial decision-making is an important issue around the world. The current study investigated this matter using both qualitative and quantitative approaches. Building on the concept of social capital, the qualitative study explores the financial vulnerability phenomenon in Brazil from the perspective of jeitinho—a way of getting things done by means of personal relationships. Analysis of 21 in-depth interviews provides a unique context for showing how this indigenous construct shapes marketplace and consumer practices, thus creating a mutually reinforcing cycle of financial dependency and vulnerability. A socioecological framework highlights how the interactions between personal characteristics (microsystem) and marketplace practices and social structures (meso- and macrosystems) may lead individuals to experience or avoid financial vulnerability. Values that are typical of Brazilians were also used to explain financial management behaviors, consumer resistance, and responsibility in the marketplace. Findings provide new insights for understanding financial vulnerability from a cultural perspective. It shows that consumers become indebted in order to support their relationships—sometimes using them as an excuse to justify hedonic consumption—and companies take advantage of this social reciprocity in their lending and retail practices perpetuating the cycle of dependency and vulnerability. The borrowinglending dynamic between relatives and friends is then explored in the quantitative study. The theoretical background includes discussion on materialism, consumer spending self-control, and the use of credit. A survey of 997 Brazilian adults was conducted to test two hypotheses. The evidences support that: more materialistic individuals are more likely to borrow from relatives and friends (H1) and individuals with a high level of consumer spending self-control are less likely to borrow from relatives and friends (H2). Results support the argument that both materialism and consumer spending self-control predicts borrowing behavior. Implications for public policy and suggestions for future research are then presented.